Pharmacological basis for medicinal use of Cymbopogon proximus Hochst. ex A. Rich. Essential oil in hyperactive gastrointestinal disorders - Hassan N. Althurwi; Najeeb Ur Rehman; Maged S. Abdel-Kader; Maged S. Abdel-Kader; Faisal F. Albaqami (Frontiers in Pharmacology)
BackgroundCymbopogon is used in traditional medicine in tropical and subtropical regions to treat various ailments. However, no research has yet provided a detailed pharmacodynamic explanation for its antidiarrheal and antispasmodic effects. This study aimed to evaluate the antidiarrheal and antispasmodic properties of the essential oil of Cymbopogon proximus (EOCP), with the goal of scientifically validating its traditional use in folk medicine.MethodsAn animal study of antidiarrheal activity was carried out using a castor oil-induced diarrhea model in rats, and the isolated small intestine of rats was used to investigate the specific mechanisms of the antispasmodic effects.ResultsThe EOCP, exhibited a protective effect against castor oil-induced diarrhea in rats at 100 and 200 mg/kg, similar to the standard drug, dicyclomine. In rat ileum preparations, EOCP decreased the basal tonus with a maximal response of (Rmax; % of ACh.-contraction) of 18.5% ± 1.5% compared with 17.5% ± 2.5% achieved with dicyclomine. In contractions elicited by different agents, EOCP showed higher potency in relaxing carbachol (CCh)-induced contractions compared to those induced by high K+ concentrations. It showed a similar relaxation profile to dicyclomine but differed from the inhibitory effects of verapamil and/or atropine. Pre-incubation of isolated ileum with increasing doses of EOCP showed that at a lower concentration (0.03 mg/mL), EOCP induced a rightward parallel shift in carbachol (CCh) concentration-response curves. At a higher concentration (0.1 mg/mL), it caused a non-parallel shift with a reduction in the maximum response, similar to the effects of dicyclomine, a dual inhibitor of muscarinic receptors and Ca++ channels. The Ca++ channel inhibitory effect of EOCP was confirmed by its rightward shift of Ca++ concentration-response curves and suppression of the maximal response, resembling the effects of verapamil, a well-established Ca++ antagonist.ConclusionThese results suggest that EOCP produces antidiarrheal and antispasmodic effects, possibly mediated via direct effect on intestinal smooth musclesf followed by dual inhibition of muscarinic receptors and Ca++ channels, thus providing a pharmacological basis for its traditional use in hyperactive gut disorders such as diarrhea and spasms.